The poetics of unremembered acts : reading, lyric, pedagogy - McGrath, Brian, 1973- (Northwestern University Press, 2013)
Poems - specifically romantic poems, such as those by Thomas Gray, William Wordsworth, and John Keats - link what goes unremembered in our reading to ethics. In "Tintern Abbey," for example, Wordsworth finds in "little . . . unremembered . . . acts" the chance to hear the "still, sad music of humanity." In this book, the author shows that poetry’s capacity to address its reader stages an ethical dilemma of continued importance. Situating romantic poems in relation to Enlightenment debate over how to teach reading - specifically, debate about the role of poetry in the process of learning to read - this book develops an alternative understanding of poetry’s role in education. The author also explores the ways poetry makes ethics possible through its capacity to pass along what we do not remember and cannot know about our reading.